Conference Organisation - Challenging Glass (Challenging Glass Conference, 2018)
CONFERENCE ORGANISERS Dr Christian Louter Delft University of Technology, Delft, The Netherlands Dr Freek Bos Eindhoven University of Technology, Eindhoven, The Netherlands Prof. Jan Belis Ghent University, Ghent, Belgium